ANALISIS LOKASI DAN KUALITAS PELAYANAN DALAM MENENTUKAN KEPUASAN KONSUMEN DENGAN MEDIASI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA RUMAH MAKAN BIRU DAUN DI KABUPATEN SITUBONDO - Majid, Fathul; Ediyanto, Ediyanto; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is a social and managerial process by which individuals or groups get what they need and what they want through the creation, offering, and exchange of everything of value with another person or society.Whether Location has a significant effect on Purchasing Decisions. Population This study used a simple random sampling method by distributing questionnaires to customers or consumers at the Biru Daun Restaurant. The purpose of this study is to determine data analysis and hypothesis testing in this study using the Structural Equation Model – Partial Least Square (PLS-SEM). Based on hypothesis tests using the SMART PLS 3.0 application, it shows that Location has a significant positive effect on purchasing decisions. The quality of service has a significant positive effect on purchasing decisions. Location has a positive but insignificant effect on customer satisfaction. Service quality has a positive but insignificant effect on customer satisfaction. Purchasing decisions have a significant positive effect on consumer satisfaction. Location to Consumer satisfaction through purchasing decisions has a significant positive effect. The quality of service to customer satisfaction through purchasing decisions has a significant positive effect.